The Reform Agenda - Stephanou, Constantinos (World Bank, Washington, DC, 2012)
The financial crisis has prompted a shift toward a tighter and more macro-prudential approach to financial regulation. But the reform agenda still needs to address the role of supervisory (rather than regulatory) failures, while the institutional arrangements needed to implement the new framework remain to be worked out. For most emerging economies, the existing reform agenda, developing institutional and legal underpinnings for the financial system and promoting financial access, remains valid. But for those characterized by weak financial oversight structures and more volatile economic cycles, adopting capital buffers as part of a macro-prudential regime may be a useful complement.